(untitled) (Global Journal of Human-Social Science, 2016)
Genetically modified organisms (GMOs) are those whose genetic material has been manipulated "artificially" in a laboratory through genetic engineering. This relatively new science creates unstable combinations of plant, animal, bacterial, and viral genes that do not occur in nature or through traditional crossbreeding methods (Non-GMO Project, 2015). With so many food options available, the aim of this study is to explore food purchasing trends of college students to determine how awareness of GMOs affects their likelihood of buying non-GMO products. Data were collected from 214 students at a southern university, using an electronic questionnaire. Results showed that even prior to survey completion; students had a relatively good knowledge of GMOs. They also felt this information would increase their likelihood of buying non-GMO products. In terms of cost, the majority agreed they would purchase non-GMO products if prices were lower. Additionally, most respondents disagreed when asked whether gender affected their perception of GMOs. Ideas for further research were also explored.